Characterization of hemolymph phenoloxidase activity in two Biomphalaria snail species and impact of Schistosoma mansoni infection. Issue 1 (December 2016) - Le Clec'h, Winka; Anderson, Timothy; Chevalier, Frédéric
Abstract Background Biomphalaria snails are the intermediate host of the blood flukeSchistosoma mansoni, which infect more than 67 million people in tropical areas. Phenoloxidase enzymes (POs), including tyrosinases, catecholases, and laccases, are known to play a role in the immune defenses of arthropods, but the PO activity present inBiomphalaria spp . hemolymph has not been characterized. This study was designed to characterize substrate specificity and reaction optima of PO activity inBiomphalaria spp. hemolymph as a starting point to understand the role of this important invertebrate enzyme activity in snail biology and snail-schistosome interactions. Methods We used spectrophotometric assays with 3 specific substrates (L-tyrosine for tyrosinase, L-DOPA for catecholase, and PPD for laccase) and diethylthiocarbarmate (DETC) as specific PO inhibitor to characterize PO activity in the hemolymph of uninfected snails from twoBiomphalaria species, and to determine the impact of the parasiteSchistosoma mansoni on the PO activity of itsB. glabrata vector. Results We identified laccase activity in hemolymph from uninfectedB. glabrata andB. alexandrina. For both species, the activity was optimal at 45 °C and pH 8.5, and located in the plasma. TheK m andV max of PO enzymes are 1.45 mM and 0.024 OD.min-1 forB. glabrata, and 1.19 mM and 0.025 OD.min-1 forB. alexandrina . When the snail vector is parasitized byS. mansoni, we observed a sharp reduction in laccase activity seven weeks after snail infection. Conclusions We employed a highly specific spectrophotometric assay using PPD substrate which allows accurate measurement of laccase activity inBiomphalaria spp. hemolymph. We also demonstrated a strong impact of the parasiteS. mansoni on laccase activity in the snail host.